Bioavailability study of paracetamol tablets in saliva and urine - Retaco, Patricia Alejandra (1996)
A bioavailability study of two lots of paracetamol tablets was carried out in 5 healthy volunteers, using a crossover aleatory design, and drug monitoring in urine and saliva by high performance liquid chromatography (HPLC). Results were correlated with those obtained in an in vitro dissolution study. Statistical evaluation of bioavailability parameters indicates that the two formulations may be considered bioequivalent, in spite of differences found during early stages of the absorption process, which were preventable according to an in vitro dissolution study.